Combined utilization of nutrients and sugar derived from wheat bran for d-Lactate fermentation by Sporolactobacillus inulinus YBS1-5. (April 2017) - Li, Jiahuang; Sun, Junfei; Wu, Bin; He, Bingfang
Graphical abstract: Highlights: S. inulinus YBS1-5 had low nutrient requirement ford -Lactate (DLA) production. Efficient nutrient recovery from wheat bran was performed by acid protease hydrolysis. Three-stage enzymatic hydrolysis of wheat bran gave a glucose yield of 93.1%. A combined use produced 99.5 g/L DLA with a yield of 0.89 g/g glucose in SHF process. DLA titer reached 87.3 g/L with wheat bran as sole feedstock in SSF process. Abstract: To decreased -Lactate production cost, wheat bran, a low-cost waste of milling industry, was selected as the sole feedstock. First, the nutrients were recovered from wheat bran by acid protease hydrolysis. Then, cellulosic hydrolysates were prepared from protease-treated samples after acid pretreatment and enzymatic saccharification. The combined use of nutrients and hydrolysates as nitrogen and carbon sources for fermentation by S. inulinus YB1-5 resulted ind -Lactate levels of 99.5 g/L, with an average production efficiency of 1.94 g/L/h and a yield of 0.89 g/g glucose. Moreover, fed-batch simultaneous saccharification and fermentation process at 40 °C, 20% (w/v) solid loading and 20 FPU/g solid cellulase concentration was obtained.d -Lactate concentrations, yield, productivity, and optical purity were 87.3 g/L, 0.65 g/g glucose, 0.81 g/L/h and 99.1%, respectively. This study provided a feasible procedure that can help produce cellulosicd -Lactate using agricultural waste without external nutrient supplementation.